Penerapan E-LKPD Interaktif Berbasis Problem Based Learning Berbantuan Liveworksheets untuk Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Fisika - Trapsilo Prihandono; Agung Supriyono; Ike Lusi Meilina; Ernasari Ernasari (JURNAL PEMBELAJARAN FISIKA, 2023)
The aim of this research is to determine the effectiveness of using Electronic Student Worksheets (E-LKS) assisted by liveworksheets based on the Problem Based Learning (PBL) model in improving critical thinking skills and learning outcomes. This research is Classroom Action Research with a One Groups Pretest-Posttest Design. The subjects of this research were all 36 students of class XI MIPA 1 SMA Negeri 1 Jember for the 2022/2023 academic year. Data collection for the critical thinking ability variable was obtained through a three-item essay test and for the learning outcome variable through a 15-item multiple choice test. The data obtained was analyzed using the N-Gain formula and the classical completeness formula. Based on the analysis, the N-Gain value for critical thinking skills was 0.531 (medium category) and learning outcomes increased with an N-Gain value of 0.26 (low category) in cycle I and 0.67 (medium category) in cycle II. Based on the results obtained, the use of multi-representation E-LKS assisted by live worksheets based on the PBL model has an effect on critical thinking skills and physics learning outcomes.